Utilization of Instagram Social Media in Public Relations Activities of PT Berau Coal to Enhance Corporate Image (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine how PT Berau Coal leverages Instagram as a social media platform within its Public Relations (PR) practices to enhance corporate image. Employing a library research method combined with content analysis of the official Instagram account @beraucoal.id, the study reveals that PT Berau Coal strategically utilizes Instagram as a primary communication channel to disseminate information related to operational activities, corporate social responsibility (CSR) programs, and environmental sustainability efforts. The digital communication strategy is delivered through a consistent visual approach, incorporating the AIDA (Attention, Interest, Desire, Action) model and narrative elements that reinforce the company’s branding. The findings indicate that Instagram effectively increases public engagement, strengthens corporate reputation, and shapes a favorable public perception of the company. Nevertheless, challenges persist, particularly in the innovation of CSR content, which tends to be repetitive. This study underscores the pivotal role of social media in adaptive, two-way communication strategies within digital PR.